Transonic Flow past the Two-Dimensional Wedge with Detached Shock Wave-Part I (日本航空学会誌, 1956)
The so-called Tricomi's equation for the stream function is solved analytically, subject to the boundary conditions prescribed along the axis of the symmetry, the surface of the wedge, the sonic line and the shock polar in the small disturbance plane. The system of the linear equations for the unknown coefficients of the solution is reduced from the boundary conditions along the sonic line and the shock polar. Solving these linear equations, the solution is determined and the flow patterns in the physical plane are obtained from the hodograph plane. In the analysis the wedge angle and the free stream Mach number are not involved separately but the solutions are represented by the transonic similarity parameter only.